Endovascular intervention with intravascular ultrasound guidance of very early dissection complication in transplant renal artery: a case report and literature review - Vu, Vu Hoang; Nguyen, Nghia Thuong; Nguyen, Chinh Duc; Nguyen, Khang Duong; Truong, Binh Quang (Frontiers in Cardiovascular Medicine, 2024)
Background Transplant renal artery dissection (TRAD) is a rare and serious event that can cause allograft dysfunction and eventually graft loss. Most cases are managed by operative repair. We report a case of TRAD in the early postoperative period, which was successfully managed with intravascular ultrasound-assisted endovascular intervention. Case presentation A 38-year-old man underwent HLA-compatible living kidney transplantation. The allograft had one renal artery and vein, which were anastomosed to the internal iliac artery and external iliac vein, respectively. Doppler ultrasonography performed a day after the operation showed an increase in systolic blood velocity, with no observed urine output and raising a suspicion of arterial anastomotic stenosis. Angiography showed a donor renal artery dissection distal to the moderately stenosed anastomosis site with calcified atherosclerotic plaque confirmed by IVUS. The transplant renal artery lesion was intervened with a stent. After the intervention, Doppler US revealed that the blood flow of the renal artery was adequate without an increase in the systolic blood velocity. Urine output gradually returned after 3 weeks, and serum creatinine level was normalized after 2 months. Conclusions Transplant recipients commonly have atherosclerosis and hypertension, which are risk factors for arterial dissection. Our case showed that endovascular intervention can replace surgery to repair very early vascular complications such as dissection and help patients avoid high-risk operations. Early diagnosis and IVUS-assisted intervention with experienced interventionists can save allograft dysfunction.